A case study for project and portfolio management information system selection: a group AHP-scoring model approach. (8th October 2010) - Gerogiannis, Vassilis C.; Fitsilis, Panos; Voulgaridou, Dimitra; Kirytopoulos, Konstantinos A.; , Evi Sachini
Features variety, variations among organisations' needs and the plethora of powerful project and portfolio management (PPM) information systems in the market, make the selection process among various PPM information systems a complicated process. The large number of the evaluation criteria involved during the decision aggravates the problem. This paper addresses the limitation of the number of criteria in such complex decision problems. It develops a hybrid model that exploits the benefits of the group analytic hierarchy process (GAHP) along with the simplicity of the scoring model for justifying the final selection. The proposed approach permits consideration of much more criteria than the typical AHP approach can reasonably handle and takes into account experts' opinions for the comparison of the PPM information systems as well as users' opinions on specific preferences/ needs. The proposed approach is applied on a real case in a public Greek organisation.